Co-occurrence of antibiotic residues and Antimicrobial resistance genes in animal manure and agricultural soils from Machakos, Kiambu, and Kajiado Counties, Kenya - Richard M. Machoka; Florence Ng’ong’a; Christabel Muhonja; Heshborne Tindih; Zachary Getenga; Sören Thiele-Bruhn (PLoS ONE, 2026)
The excessive and often unregulated use of antibiotics in livestock production and human health has led to the dissemination of antibiotic residues and antibiotic resistance genes (ARGs) posing a serious threat to the environment and public health. This study investigates the co-occurrence and spatial distribution of antibiotic residues and ARGs in livestock manure and agricultural soils from Machakos, Kiambu, and Kajiado counties in Kenya, regions characterized by intensive livestock farming. A total of 180 animal manure and soil samples from 30 farms across the three counties were collected and pooled into 18 samples. Antibiotic residues were extracted and quantified using high-performance liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). Nine ARGs ( aadA, ermB , sul1, tetQ, tetW, dfrA1, blaMOX, blaOXA and qnrB were quantified via absolute and relative qPCR, normalized to 16S rRNA gene copy numbers. Multivariate analyses, including PCoA and Spearman Correlation, were conducted to explore ARG structure and co-occurrence. Tetracycline, particularly oxytetracycline, was the most abundant antibiotic in manure (up to 1150 ng mL −1 ), especially in pig manure from Kiambu. Sulfadimethoxine was undetectable in nearly all samples except in soil mixed with pig manure from Kajiado county, which showed a concentration above 70 ng mL −1 , the pig manure from the same county had levels below 2 ng mL −1 . Sulfadimidine, sulfamethoxanole and erythromycin were not detected in any of the samples. A three-way ANOVA showed that animal source (cattle, pigs, poultry) and sample type (manure, soil) were generally not significant factors for antibiotic concentration. Only oxytetracycline (P = 0.0421, 0.0901) and sulfadimethoxine (P = 0.0904, 0.044, 0.054) showed marginal significance by sample type (P = 0.0785). Antibiotic resistance genes were widely distributed, with aadA, ermB and sul1 being the most prevalent, especially in soils from Kiambu and Machakos. The tetQ showed extremely high relative abundance, indicating intense selection pressure from tetracyclines. Strong positive correlations were observed between co-occurring ARGs, including tetQ and tetW as well as erm and sul1 . The concurrent detection of persistent antibiotic residues and high ARG loads in both manure and soils underscores the urgent need for improved antibiotic stewardship, sustainable manure management, and environmental monitoring in Kenyan agroecosystems.